Enhanced sulfur in the upper troposphere and lower stratosphere in spring 2020 - L. Tomsche; L. Tomsche; A. Marsing; A. Marsing; T. Jurkat-Witschas; J. Lucke; J. Lucke; S. Kaufmann; K. Kaiser; J. Schneider; M. Scheibe; H. Schlager; et al. (Atmospheric Chemistry and Physics, 2022)
Sulfur compounds in the upper troposphere and lower stratosphere (UTLS) impact the atmosphere radiation budget, either directly as particles or indirectly as precursor gas for new particle formation. In situ measurements in the UTLS are rare but are important to better understand the impact of the sulfur budget on climate. The BLUESKY mission in May and June 2020 explored an unprecedented situation. (1) The UTLS experienced extraordinary dry conditions in spring 2020 over Europe, in comparison to previous years, and (2) the first lockdown of the COVID-19 pandemic caused major emission reductions from industry, ground, and airborne transportation. With the two research aircraft HALO and Falcon, 20 flights were conducted over central Europe and the North Atlantic to investigate the atmospheric composition with respect to trace gases, aerosol, and clouds. Here, we focus on measurements of sulfur dioxide (SO2) and particulate sulfate (SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="63f11f9b60a09208ebeae789905b238b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-15135-2022-ie00001.svg" width="13pt" height="17pt" src="acp-22-15135-2022-ie00001.png"/></svg:svg>) in the altitude range of 8 to 14.5 km which show unexpectedly enhanced mixing ratios of SO2 in the upper troposphere and of SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="6734be199742c3e7a0dfe877974848e8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-15135-2022-ie00002.svg" width="13pt" height="17pt" src="acp-22-15135-2022-ie00002.png"/></svg:svg> in the lowermost stratosphere. In the UT, we find SO2 mixing ratios of (0.07±0.01) ppb, caused by the remaining air traffic, and reduced SO2 sinks due to low OH and low cloud fractions and to a minor extent by uplift from boundary layer sources. Particulate sulfate showed elevated mixing ratios of up to 0.33 ppb in the LS. We suggest that the eruption of the volcano Raikoke in June 2019, which emitted about 1 Tg SO2 into the stratosphere in northern midlatitudes, caused these enhancements, in addition to Siberian and Canadian wildfires and other minor volcanic eruptions. Our measurements can help to test models and lead to new insights in the distribution of sulfur compounds in the UTLS, their sources, and sinks. Moreover, these results can contribute to improving simulations of the radiation budget in the UTLS with respect to sulfur effects.